Michel Foucault e o "cuidado de si": a invenção de formas de vida resistentes na educação / Michel Foucault and "care of the self: the invention of resistant forms of life in education - Alexandre Simao Freitas (Universidade Estadual de Campinas, 2010)
O objetivo principal da reflexão aqui proposta é explorar uma face ainda pouco abordada, pelo campo educacional, da experiência intelectual do pensador francês Michel Foucault: o cuidado de si e a criação de novas formas de vida. A questão problematizada corresponde aos processos de subjetivação por meio das chamadas "práticas de si", contribuindo para elucidar alguns aspectos das condições de formação do ser humano na contemporaneidade. A analítica do cuidado de si, no âmbito da leitura foucaultiana do texto "Alcibíades", no curso Hermenêutica do Sujeito, é apontada como uma potência instituinte imanente à vida, evidenciando como a experiência ética que o sujeito faz de si mesmo é inseparável do processo político de sua formação. Abstract The main objective of reflection proposed here is to explore a face underexplored, by the educational field, of the intellectual experience of the french philosopher Michel Foucault: care of the self and the creation of new life forms. The problematic question corresponds to the subjective processes by self practices, elucidating some of the conditions of human formation in contemporary society. The analytics of care of the self, in context the foucaultian reading of the text Alcibíades, in the course Hermeneutics of the Subject, is considered a power immanent to life, showing how the ethical experience that the subject makes of itself is inseparable from political formation.